Finite Element Analysis of Piezoelectric Composite with Negative-stiffness Inclusions Considering Imperfect Bonding - Oo, Khin Lae Lae; Sapsathiarn, Yasothorn; Wang, Yun-Che (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Piezoelectric materials, known for their electromechanical properties, are crucial in applications like structural health monitoring, sensors, actuators, and energy harvesting. This study presents a finite element-based micromechanical analysis to determine the effective properties of piezoelectric composites with varying fiber volume fractions. Boundary conditions for the representative volume element (RVE) are carefully examined to ensure periodicity and accuracy. The analysis is validated by comparing electromechanical coupling properties with previous studies. The study explores the potential of metamaterial properties in piezocomposites by incorporating negativestiffness inclusions and considering the effect of imperfect bonding between the fiber and matrix. These factors can lead to unconventional mechanical behavior, such as enhanced flexibility or tunable stiffness, significantly improving performance for specific applications. By investigating these elements, the study offers valuable insights into the macroscopic properties of piezocomposites, essential for optimizing their design and performance across a wide range of engineering applications.